Food security and the ultra poor - Halder, Shantana R. (Research and Evaluation Division, Brac, 2019)
This paper aims to derive some policy guidelines by analysing factors affecting food security of the ultra poor. Here more emphasis is given on the number of rice meals taken and the sources of rice consumed during the last 24 hours. Results show that only 17% of the ultra poor had the capacity to purchase rice for three meals a day. Twenty percent had to depend on help from others. One-fourth had only one rice meal, managed through any source. Food security was found to be highly correlated with household landholding, adult literacy, household asset base, per capita income and male female participation rate in the labour force. Differences in the level of economic development of specific region also had significant effect on food security. The disabled and elderly people are identified as a highly food insecure group. For ensuring food creation of wage employment opportunities can help those who are capable of working. For the elderly and disabled, there should be some provision of safety nets.